Carcinosarcoma of ovary - a rare case report and literature overview - Pushpagiri, Niroopama; Dinakaran, Shanthi; Chidambaram, Alagamai; Pari, Priya (International Journal of Advances in Medicine, 2017)
Ovarian carcinosarcoma is one of the lethal malignant tumours of the female genital system. It is extremely rare and represents 1% of all malignant ovarian tumours. It occurs most commonly in postmenopausal women with the incidence peak in sixth decade. Our reported case was a 41 years nulliparous lady who presented with abdominal distension for one month. Physical examination revealed a huge non tender abdomino-pelvic mass suspected to be of ovarian origin. She was investigated and radiological studies confirmed a left ovarian cystic mass of 26 cm x 22 cms with solid enhancement. Calculated RMI was 66. Staging laparotomy was performed and tense smooth surface cystic mass arising from left ovary was found and removed intact. Total abdominal hysterectomy, salpingo-oophorectomy, infracolic omentectomy was done along with the peritoneal, lymph node biopsies and peritoneal washings for cytology. The presentation and findings were indistinguishable from epithelial ovarian neoplasm. Histo-pathology revealed carcinosarcoma of ovary with positive peritoneal cytology. Staged as IC according to FIGO criteria. The patient was given 6 cycles of adjuvant chemotherapy with carboplatin and ifosfamide and was in good health at the time of follow up visits.